The Student Police Program as an Effort to Reduce Traffic Violations by High School Students - Deka Oktaria Pertiwi (Advances in Police Science Research Journal, 2024)
In the last 4 years, The background to this problem arises because the level of traffic violations in the Kuningan region continues to increase every year and is mostly committed by high school students. In an effort to reduce these violations, the Dikyasa unit established a Student Police (Poljar) program to provide orderly education of traffic. This study aims to analyze how the implementation of the Student Police program, as well as what factors influence the non-optimal implementation of the Student Police program as an effort to reduce traffic violations. This study uses theory and concepts to analyze the focus of research. Theories used include Law Enforcement Theory and Management Theory. Research concepts include Optimization, Community Education in the Field of Traffic (Dikmas Lantas), Traffic Violations, and Students. The study was conducted with a qualitative approach. This type of research is descriptive analytic. Primary, secondary and tertiary data sources. Data collection techniques with interviews, observation, and study documents. And data validity with source triangulation and technique triangulation. Data analysis techniques with data reduction, data presentation, and drawing conclusions. The results found that traffic violations in the Kuningan area were dominated by high school students. The violation is influenced by the legal factors themselves, the law enforcement factors, the supporting Sarpras factors, community factors, and cultural factors. The implementation of the Student Police Program is also not optimal due to several inhibiting factors that influence its implementation. Research suggestions to optimize the implementation of the Student Police Program (1) carry out regular analysis and evaluation, (2) expand the object of the implementation of community education then, (3) build good coordination among personnel, (4) increase activities involving students.